Efeitos do óleo da semente de neem (Azadirachta indica A. Juss) nos ovócitos e glândulas salivares de carrapatos Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) - Remedio, Rafael Neodini [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Rhipicephalus sanguineus ticks have attracted, in recent years, the attention of researchers as well as public health managers, since they have become major urban pests, transmitters of diseases to humans and dogs. For this reason, the search for formulations with acaricide action has been constant concern of veterinary pharmaceutical industries. However, the vast majority of products currently commercialized exhibits high toxicity to the hosts of these ectoparasites and to the environment, even inducing resistance in ticks. Alternative control methods such as the use of plant extracts, for example, have become increasingly interesting, since they have reduced costs and low toxicity. In this sense, Azadirachta indica (neem) species stands out, as its leaf and seed extracts have recognized repellent, insecticide and acaricide potential. Thus, this study aimed to evaluate the morphological alterations resulting from the action of neem in the ovary and salivary glands of semi-engorged R. sanguineus female ticks, subjected to the topical application of the oil extracted from neem seeds, at concentrations of 20, 40 and 60%, using 10% aqueous ethanol as solvent. The organs were collected and fixed, and analyzed by means of techniques in conventional light microscopy, confocal laser scanning microscopy and transmission electron microscopy. In general, the methodology proposed in this work allowed the simulation of a topical treatment of the infested animals, making the results closer to a practical application in field. In both analyzed organs, neem oil clearly demonstrated a dose-dependent effect. Oocytes and glandular acini of R. sanguineus ticks exhibited similar morphological changes, such as evident signs of cytoplasmic disorganization, cellular vacuolation, nuclear or nucleolar irregularities, dilation of mitochondrial cristae, as well as dilation in rough endoplasmic reticulum lumen. These facts show that, regardless of the organ, neem ...

Os carrapatos Rhipicephalus sanguineus têm atraído, nos últimos anos, a atenção de pesquisadores, bem como de órgãos gerenciadores da saúde pública, por estarem se tornando grandes pragas urbanas, transmissoras de doenças para cães e humanos. Por esta razão, a busca por formulações com ação acaricida tem sido preocupação constante das indústrias farmacêuticas veterinárias. No entanto, a grande maioria dos produtos atualmente comercializados apresenta alta toxicidade aos hospedeiros dos ectoparasitas e ao meio ambiente, induzindo, inclusive, resistência nos carrapatos. Métodos alternativos de controle, como o uso de extratos de plantas, por exemplo, têm se tornado cada vez mais interessantes, já que apresentam menores custos e baixa toxicidade. Neste sentido, destaca-se a espécie Azadirachta indica (neem), cujos extratos de folhas e sementes apresentam reconhecido potencial repelente, inseticida e acaricida. Desta forma, este estudo teve como objetivo avaliar as alterações morfológicas observadas no ovário e nas glândulas salivares de fêmeas semiingurgitadas de carrapatos R. sanguineus, submetidas à aplicação tópica do óleo extraído das sementes de neem, nas concentrações de 20, 40 e 60%, utilizando-se etanol aquoso a 10% como solvente. Os órgãos foram coletados, fixados, e analisados por meio de técnicas de microscopia de luz convencional, microscopia confocal de varredura a laser e microscopia eletrônica de transmissão. De forma geral, a metodologia proposta neste trabalho permitiu a simulação de um tratamento tópico dos animais infestados, tornando os resultados obtidos mais próximos de uma aplicação prática em campo. Em ambos os órgãos analisados, o óleo de neem demonstrou efeitos claramente dose-dependentes. Os ovócitos e os ácinos glandulares de carrapatos R. sanguineus exibiram alterações morfológicas semelhantes, tais como sinais evidentes de desorganização citoplasmática,...
Keywords: Mites; Ácaro; Carrapato; Acaricidas; Extratos vegetais; Nim; Ovarios; Glandulas salivares; Morfologia